INOVASI DALAM PEMBELAJARAN AKUNTANSI LANJUTAN UNTUK MENINGKATKAN KOMPETENSI MAHASISWA - Elisabeth Margareta; Febriana Jovanka Gultom; Gladis Rebeka Sinaga; Jesika Angelina Damanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Accounting is a scientific discipline that is not enough to understand only through theory, but will be easier to understand if practiced directly in real bookkeeping. Therefore, developing accounting practicum teaching materials is one of the stepstaken to improve student competency. It is believed that by implementing appropriate learning innovations and learning packages that reflect real situations, student understanding of the material can increase, which ultimately has an impact on increasing competency. This research aims to develop an innovative accounting practicum learning package as a strategy to improve the quality of financial accounting and tax accounting learning in order to strengthen student competence. In this research, we will analyze how learning innovations and accounting practicum learning packages are most suitable for application in accounting study programs. In line with the development of the role of accounting in the industria world, graduates are expected to have competencies that suit the needs of workforce users. The results of this research are in the form of learning innovation concepts and accounting practicum learning packages. However, these findings still require further testing before they can be generalized.